2010
DOI: 10.17221/88/2010-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Equine cyathostomosis: case reports

Abstract: ABSTRACT:Twelve clinical cases of cyathostomosis in horses treated at the Equine Clinic University of Veterinary and Pharmaceutical Sciences in Brno, the Czech Republic, between the years 1999 and 2008 are described in this report. Six cases (50%) were hospitalized in the period from 2007 to 2008. Eleven of them were hospitalized in the period from December to March. Only one case was admitted in June, but the clinical signs had appeared for the first time in January. All horses described in these cases were y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 17 publications
3
22
0
2
Order By: Relevance
“…Cyanthosomes are non-migrating parasites that live in the large intestine of donkeys, horses and zebra (Matthee et al 2000;Bodecek et al 2010). Adult small strongyles live in the large intestine particularly the cecum of donkeys.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyanthosomes are non-migrating parasites that live in the large intestine of donkeys, horses and zebra (Matthee et al 2000;Bodecek et al 2010). Adult small strongyles live in the large intestine particularly the cecum of donkeys.…”
Section: Discussionmentioning
confidence: 99%
“…However, some investigators previously considered cyathostomes as parasites with minimal pathogenic influence on the horses and donkeys (Lyons et al 1999) but, it has been shown that small strongyles create reactions such as catarrhal inflammation, hemorrhagic typhlitis or fibrinous enteritis in the cecum or other parts of the large intestine that may result in intestinal ulcers and possible perforation of the intestinal wall. The larvae of small strongyles encyst or burrow into deeper parts of the large intestine and this encysted stage remains for long periods of time and produces nodules in the deeper layers (Bodecek et al 2010). In some instances larval cyathostomins is associated with the sudden development of large numbers of cyathostome larvae in the wall of the large intestine and further severe clinical signs and advanced pathological changes.…”
Section: Introductionmentioning
confidence: 99%
“…En la histopatología, puede haber una respuesta celular inflamatoria con poblaciones mixtas de células mononucleares y polimorfonucleares (Corning, 2009). En otros estudios se observó enteritis hemorrágica o fibrinosa en el ciego (Bodecek et al, 2010), enteritis no supurativa e infiltración de eosinófilos, linfocitos y macrófagos en la mucosa intestinal y submucosa, así como granulomas focales y multifocal en el intestino grueso (Oryan et al, 2013).…”
Section: Discussionunclassified
“…Microscopy for parasite eggs should be performed. Definitive diagnosis of larval cyathostominosis is sometimes challenging because the disease is caused by encysted larval stages of the parasite, meaning faecal examination can be unhelpful (Bodecek et al, 2010). Cyathostomin larvae may be visible by eye in the faeces or on the glove after rectal examination.…”
Section: Diagnostic Testingmentioning
confidence: 99%